Autopsi Forensik pada Kasus Tenggelam: Mengungkap Peran Trauma Tumpul dan Perdarahan Subarachnoid sebagai Penyebab Kematian - Ramadhan, Al-Fath; Mansyur, Mauluddin; Mathius, Denny; Assegaf, Zulfikar Gaffar (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Drowning-related deaths are often associated with asphyxia due to fluid aspiration into the airways. However, in some cases, the primary cause of death is not drowning itself but rather preceding trauma. This report discusses the case of a man found drowned, where forensic examination revealed extensive subarachnoid hemorrhage caused by severe blunt head trauma. External examination showed livor mortis that did not blanch with pressure, bruises on several parts of the body, and abrasions on the face and extremities. Internal examination revealed cerebral edema and increased intracranial pressure compressing the brainstem. Typical signs of drowning, such as abundant foam in the airways or significant pulmonary edema, were absent. Based on forensic findings, the primary cause of death was respiratory failure due to subarachnoid hemorrhage, rather than drowning. These results highlight the importance of further investigation to determine whether the trauma resulted from an accident or an act of violence before the victim entered the water.